Development of a Conceptual Framework to Measure the Social Impact of Burns. Issue 6 (November 2016) - Marino, Molly; Soley-Bori, Marina; Jette, Alan M.; Slavin, Mary D.; Ryan, Colleen M.; Schneider, Jeffrey C.; Resnik, Linda; Acton, Amy; Amaya, Flor; Rossi, Melinda; Soria-Saucedo, Rene; Kazis, Lewis E.
Abstract : Measuring community reintegration following burn injury is important to assess the efficacy of therapies designed to optimize recovery. This project aims to develop and validate a conceptual framework for understanding the social impact of burn injuries in adults. The framework is critical for developing the item banks used for a computerized adaptive test. We performed a comprehensive literature review and consulted with clinical experts and burn survivors about social life areas impacted by burn injury. Focus groups with burn survivors and clinicians were conducted to inform and validate the framework. Transcripts were coded using grounded theory methodology. The World Health Organization's International Classification of Functioning, Disability and Health, was chosen to ground the content model. The primary construct identified was social participation, which contains two concepts: societal role and personal relationships. The subdomains chosen for item development were work, recreation and leisure, relating with strangers, and romantic, sexual, family, and informal relationships. Qualitative results strongly suggest that the conceptual model fits the constructs for societal role and personal relationships with the respective subdomains. This conceptual framework has guided the implementation of a large-scale calibration study currently underway which will lead to a computerized adaptive test for monitoring the social impacts of burn injuries during recovery.